2011
DOI: 10.1089/gtmb.2010.0260
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Association ofEPHX1Genotypes and Haplotypes with Oral Cancer in South Indians

Abstract: As genetic variation is thought to contribute to the etiology of oral cancer, microsomal epoxide hydrolase (EPHX1) was chosen as a candidate gene. This study thus sought to investigate possible genetic associations between the rs1051740, rs2292566, and rs2234922 polymorphisms of EPHX1 and oral cancer. Oral cancer patients (n=157) and healthy control subjects (n=132) were screened for the genotypes using TaqMan allelic discrimination. The associations between genotypes, alleles, and haplotypes of the three muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Eight articles [ 24 – 29 , 31 32 ] included in this meta-analysis described 9 case-control studies, with 1890 cases and 1894 controls, revealing an association between the EPHX1 Tyr113His polymorphism and HNC susceptibility. The main results of this pooled analysis are presented in Table 2 and Fig 2 shows forest plots illustrating the effect of the EPHX1 Tyr113His polymorphism on HNC risk.…”
Section: Resultsmentioning
confidence: 99%
“…Eight articles [ 24 – 29 , 31 32 ] included in this meta-analysis described 9 case-control studies, with 1890 cases and 1894 controls, revealing an association between the EPHX1 Tyr113His polymorphism and HNC susceptibility. The main results of this pooled analysis are presented in Table 2 and Fig 2 shows forest plots illustrating the effect of the EPHX1 Tyr113His polymorphism on HNC risk.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, 32 studies not in HWE and 39 with less 100 patients were also deleted. Hence, 45 studies [ 8 - 10 , 23 - 63 ] for Tyr113His polymorphism (20,091 cases and 27,396 controls) and 54 studies [ 8 - 10 , 24 - 26 , 28 , 29 , 32 , 34 - 45 , 47 - 51 , 53 , 55 - 61 , 63 - 81 ] for His139Arg polymorphism (19,437 cases and 27,289 controls) were included eventually. Genotype distributions in the controls of all selected studies are in agreement with HWE.…”
Section: Resultsmentioning
confidence: 99%
“…The findings from some previous studies suggested that genetic polymorphism in EPHX1 has important roles in the development of cancers [ 55 , 86 - 88 ]. However, others reported no association of EPHX1 polymorphisms with risk of cancers [ 24 , 26 , 34 , 45 ]. This inconsistency may be due to tremendous difference in sample size, diverse ethnic background, sampling bias, publication bias, or inadequate statistical power.…”
Section: Discussionmentioning
confidence: 99%
“…The findings from some previous studies suggested that genetic polymorphism in EPHX1 has important roles in the development of cancers [55,[86][87][88]. However, others reported no association of EPHX1 polymorphisms with risk of cancers [24,26,34,45]. This inconsistency may be due to tremendous difference in sample size, diverse ethnic background, sampling bias, publication bias, or inadequate statistical power.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, 32 studies not in HWE and 39 with less 100 patients were also deleted. Hence, 45 studies [8][9][10] for Tyr113His polymorphism (20,091 cases and 27,396 controls) and 54 studies [8][9][10][24][25][26]28,29,32,[34][35][36][37][38][39][40][41][42][43][44][45][47][48][49][50][51]53,[55][56][57][58][59][60][61][63][64][65][66][67][68][69][70][71][72][73][74][75][76]…”
Section: Study Characteristicsmentioning
confidence: 99%